2020
DOI: 10.1061/(asce)gm.1943-5622.0001729
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Evaluation of Ballasted Track Substructure Response under Repeated Train Loads

Abstract: The irrecoverable deformations in the substructure layers are detrimental to the track stability and demand frequent maintenance. With an escalation in axle-load and traffic volume, the frequency of maintenance operations has remarkably increased. Consequently, there is an inevitable need to predict the long-term behavior of the track substructure layers.This article presents a methodology to evaluate the recoverable and irrecoverable responses of the substructure layers under the train-induced repetitive load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…In the theoretical approach, the track modulus is evaluated by dividing the system support stiffness 39 with the sleeper spacing. The system support stiffness ( k t ) is evaluated as the series equivalent of the stiffness of the rail pad ( k p ), ballast ( k b ), subballast ( k s ) and subgrade ( k g ) layers 34 1kt=1kp+1kb+1ks+1kg…”
Section: Model Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the theoretical approach, the track modulus is evaluated by dividing the system support stiffness 39 with the sleeper spacing. The system support stiffness ( k t ) is evaluated as the series equivalent of the stiffness of the rail pad ( k p ), ballast ( k b ), subballast ( k s ) and subgrade ( k g ) layers 34 1kt=1kp+1kb+1ks+1kg…”
Section: Model Descriptionmentioning
confidence: 99%
“…To evaluate the vibrating mass and stiffness of the substructure layers, pyramidal distribution of vertical load from the sleeper bottom to the track substructure layers is assumed, which incorporates the overlapping of the load distribution pyramids along both longitudinal (i.e., the direction of train movement) and transverse directions 34 . Figure 4 illustrates the effective region of the load distribution pyramids beneath each sleeper position.…”
Section: Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The displacements of the granular layers (ballast or subballast) also depend on the underlying subgrade type. Punetha et al (2020a) observed that the deformations in the ballast and the subballast layers in an open track are much higher when the subgrade soil is stiff compared to the case when the subgrade soil is soft. However, the influence of subgrade soil properties on the performance of the transition zones is not yet fully perceived.…”
Section: Introductionmentioning
confidence: 96%
“…Most studies addressing track settlements at transition zones considering the train-track interaction have used simplified 1D Winkler type models coupled with empirical settlement formulas, as in (Mauer, 1995;Hunt, 1997;Kempfert and Hu, 1999;Varandas et al, 2014a). However, because 1D Winkler models require extensive calibration of material parameters and other modeling aspects, such as equivalent springs and dampers (Punetha et al, 2020), its application to real scenarios or to perform parametric studies has been somewhat limited.…”
Section: Introductionmentioning
confidence: 99%